Finite Element Analysis and Lightweight Design of Hydro Generator Lower Bracket - Liao, Yongyi; Liao, Baiyu (Manufacturing Technology Journal, 2020)
Lower bracket is an important component in hydro generator. Taking lower bracket as the research object, the strength, the stiffness and the dynamic characteristics of lower bracket have been simulated and analyzed by means of establishing a finite element model. With the two design indexes of maximum normal stress and stiffness as the constraint conditions, aiming at an optimized design with the minimum mass and proposed a lightweight optimization method. The design parameters of the optimized model of hydro generator lower bracket are determined by using the compound form method with optimization iteration. Through lightweight optimization design, the maximum normal stress and maximum displacement of lower bracket are within the allowable value range, modal analysis shows that the dynamic characteristics of the optimized structure also meet the requirements, with the potential of material further utilized. The lightweight optimization design reduced the weight of lower bracket in hydro generator by 790kg and the weight-loss ratio reaches 44.38%, thus achieving the purpose of lightweight. The optimization results are applied in the improvement design of lower bracket and the method is practical and suitable for engineering applications.
Keywords: Hydro generator; Lower bracket; Finite element model; Lightweight design; Optimized model